Beholding situated art and the aesthetics of reception - Wilder, Ken (Bloomsbury Visual Arts, 2020)
Beholding considers the spatially situated encounter between artwork and spectator. It argues that artworks created for specific places or conditions structure a reciprocal encounter, which is completed by the presence of a beholder. These are works which demand the'beholder's share', but not, as Ernst Gombrich famously claimed, to sustain an illusion. Rather, Beholding reconfigures Gombrich's notion of the beholder's share as a set of'licensed'imaginative and cognitive projections.Each chapter frames a particular work of art from the remit of a complementary theoretical text. The book establishes a transhistorical notion of the spatially situated encounter, and considers the role of the architectural host in bringing the beholder's orientation into play. The book engages a diverse range of practices: from Renaissance painting and group portraiture to intermedia practices of installation and performance art. Written within the broad remit of reception aesthetics, the book proposes a phenomenological theory of beholding, argued through an in-depth examination of artworks and their spatial contexts, selected for their explanatory potential. These various encounters allocate different constitutive roles to the beholder, bringing not only spatial and temporal orientation into play, but also a repertoire of anticipated ideas and beliefs.